Beverley, Bat Your Service - Collier, Kelly (New York : Atheneum Books for Young Readers, 2025)
Beverley the Bat loves entertaining but never has guests, so when a new human family moves into his big, old house, he eagerly welcomes them but soon realizes his bat-style hospitality might not align with human expectations.
new kids book 2025 fall.
Ages 4-8.
Keywords: Bats -- Fiction; Hospitality -- Fiction; Human-animal relationships -- Fiction; Animal fiction; Picture books